2015
DOI: 10.3171/2014.12.jns141699
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in high-frequency hearing loss following technical modifications to microvascular decompression for hemifacial spasm

Abstract: M icrovascular decompression (MVD) is a safe and efficacious procedure for the treatment of hemifacial spasm (HFS), a debilitating condition that reduces patients' quality of life. Severe sensorineural hearing loss (SNHL) across all frequencies is a known complication of the operation, with reported rates ranging from 1.4% to 20%. 4,12,[18][19][20][21]24 In addition to severe SNHL, however, a recent report has raised concern that as many as one-half of patients undergoing MVD for HFS may experience high-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Intermittent release of the retractor, based on the intraoperative BAEP monitoring, would also help to prevent possible hearing loss 25) . Some authors have suggested that performing the procedure without the use of fixed retraction may help reduce hearing loss 38) . We have also performed MVD surgery using a retractor, and particularly when the VA is the causative offending vessel, intermittent retraction on the cerebellum was needed to prevent the development of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent release of the retractor, based on the intraoperative BAEP monitoring, would also help to prevent possible hearing loss 25) . Some authors have suggested that performing the procedure without the use of fixed retraction may help reduce hearing loss 38) . We have also performed MVD surgery using a retractor, and particularly when the VA is the causative offending vessel, intermittent retraction on the cerebellum was needed to prevent the development of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgeons have attempted to lower these risks by using techniques such as brainstem auditory evoked potentials to minimize damage. 78 Despite these efforts, a risk of permanent cranial nerve damage remains.…”
Section: Comparative Treatmentsmentioning
confidence: 99%
“…Retraction of the cerebellum by a spatula could be the major cause of surgical complications. In our study, the surgical procedure without the use of fixed retraction may greatly reduce the occurrence of SNHL following MVD for HFS 18 19 . Fixed retraction of the cerebellum with selfretaining retractor was never used during any step of the procedure in our institution since the beginning of our use of the minimal invasive retrosigmoid approach 9 .…”
Section: Discussionmentioning
confidence: 71%